A companion to Marie de France - Whalen, Logan E. (Brill's companions to the Christian tradition ;, 2011)
After nearly eight centuries and much research and writing on Marie de France, the only biographical information we know about her, with any degree of certainty, is that she was from France and wrote for the Anglo-Angevin court of Henry II. Yet Marie de France remains today one of the most prominent literary voices of the end of the 12th century and was the first woman of letters to write in French. The chapters in this book are composed by scholars who have specialized in Marie de France studies, in most cases for many years. Offering traditional views alongside new critical perspectives, the.